Peran Petugas Lapangan Keluarga Berencana dan Pembantu Pembina Keluarga Berencana Desa dalam Mensosialisasikan Alat Kontrasepsi (Studi di Desa Kebonagung Kecamatan Sukodono Kabupaten Sidoarjo) - Evi Setyowati; Arsiyah Arsiyah; Ahmad Riyadh Umar Balahmar (Universitas Muhammadiyah Sidoarjo, 2016)
The purpose of this study was to describe the role of Family Planning and Vice builder Family Planning Villages in disseminating contraceptives in the village of the District Kebonagung Sukodono and constraints faced in the field. This study uses data source in the form of primary data and secondary data, data collection techniques by observation, interview and documentation. While the data analysis techniques used in this research is descriptive analysis with qualitative approach that includes: data collection, data reduction, data presentation and conclusion. The results indicate of this study that the role of PLKB and PPKBD have been performing their duties and functions in accordance with the rules, but there are some employees that the power of a response is slow, zoning does not fit the rules due to the small number of officers, and their dual position. So that the delivery of information to the public to experience problems. At least the officer due to their employees who retired due to age and system of recruitment moratorium and that no return.